At the table but can not break through the glass ceiling:Board leadership positions elude diverse directors - Field, Laura Casares; Souther, Matthew E.; Yore, Adam S. (Journal of Financial Economics, 2020)
We explore the labor market effects of gender and race by examining board leadership appointments. Prior studies are often limited by observing only hired candidates, whereas the boardroom provides a controlled setting where both hired and unhired candidates are observable. Although diverse (female and minority) board representation has increased, diverse directors are significantly less likely to serve in leadership positions despite possessing stronger qualifications than nondiverse directors. While specialized skills such as prior leadership or finance experience increase the likelihood of appointment, that likelihood is reduced for diverse directors. Additional tests provide no evidence that diverse directors are less effective.